2022
DOI: 10.3390/ijfs10030080
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Insurers’ Financial Insolvency on Non-Life Insurance Companies’ Profitability: Evidence from Bangladesh

Abstract: A stable and healthy insurance industry plays a vital role in sustaining an economy resistant to economic shocks by providing an efficient risk-transition mechanism. There is a relative scarcity of research inspecting the impact of insurers’ financial insolvency on the profitability of insurance firms. Employing 2011–2019 panel data of 16 non-life insurance companies operating in Bangladesh, this research endeavors to examine the impacts of insurers’ financial insolvency on the profitability of insurance compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…NL moderated by ROL in surrounding countries has decreased the EG of local countries by 2.1 percent as the only significant result. Due to inappropriate policies, the non-life insurers' financial insolvency and lower profitability may discourage the companies' growth (Siddik et al 2022;Pavia et al 2021). When considering the short-run direct impact of NL across countries on EG, there was a direct impact by PSV, which is 4.1 percent.…”
Section: Results On the Spatial Impact Of Institutions And Non-life I...mentioning
confidence: 99%
“…NL moderated by ROL in surrounding countries has decreased the EG of local countries by 2.1 percent as the only significant result. Due to inappropriate policies, the non-life insurers' financial insolvency and lower profitability may discourage the companies' growth (Siddik et al 2022;Pavia et al 2021). When considering the short-run direct impact of NL across countries on EG, there was a direct impact by PSV, which is 4.1 percent.…”
Section: Results On the Spatial Impact Of Institutions And Non-life I...mentioning
confidence: 99%
“…The result revealed that inflation is positive and statistically significant for the financial health of non-life insurance companies (Siddik et al, 2022). A negative inflation rate can be detrimental to capaccumulation (Chen et al, 2020).…”
Section: Inflationmentioning
confidence: 94%
“…From the results of this study, it can be concluded that the increase in production costs such as raw materials, labor wages, or property rent is not followed by an increase in company income projected from the return on asset ratio. According to (Siddik et al, 2022) shows that inflation has a significant negative effect on return on equity. Unexpected inflation rates affect costs, assets, liabilities, technical provisions and future claim payments that slow down company growth.…”
Section: Inflationmentioning
confidence: 99%